Electoral Law Reform in the Perspective of Responsive Justice: Comparative Law Between Indonesia, India, and Thailand - Sudarmanto, Kukuh; Pranoto, Edi; Jain, Vaibhav (Faculty of Law, Universitas Pattimura, 2025)
Introduction: Elections are a vital democratic mechanism in channeling people's voices, electing leaders, and determining policies, with the principles of transparency, fairness, and effective oversight. Although there are still challenges in citizen participation, elections play a crucial role in peaceful transitions of power and socio-political stability.Purposes of the Research: This study aims to analyze efforts to reform electoral law from a responsive justice perspective by comparing laws between Indonesia, India, and Thailand.Methods of the Research: This research is a normative legal research with a conceptual, legislative, and comparative approach.Results of the Research: Election law reform, which includes the implementation of the principles of direct, free, and fair, is needed to create a more democratic system that is responsive to social needs. In Indonesia, India, and Thailand, election law reform focuses on improving the quality of democracy, justice, and voter participation through system changes and revisions to laws. The role of the Constitutional Court and the Supreme Court in each country is very important in ensuring more transparent and fair elections, and reflecting the will of the people.